A Study of the Accuracy and Reliability of Articles about Alopecia in Newspapers - Kim, Hyojin (Ann Dermatol, 2018)
BACKGROUND: There is growing interest in alopecia among the general population. Many people obtain information from easily accessible media rather than from doctors; thus, the media can play an important role in shaping public opinion. OBJECTIVE: The goal of this study was to evaluate the content and reliability of newspaper articles on alopecia. METHODS: Newspapers were categorized into three groups: one group of print newspapers and two groups of online newspapers. Online newspapers were further divided into two groups according to type of publishing company; one publishes both print and online newspapers and the other publishes online newspapers only. The most frequently subscribed or circulated newspaper in each group was selected. Articles containing information on alopecia were selected from 3 years of each newspaper and evaluated for reliability. RESULTS: Most articles in each group used the general term “alopecia” instead of naming a specific hair loss disease. The majority of articles were based on consultation with experts. Assessment of the accuracy of articles with three grade scales showed that the percentage with high accuracy was 38.9%, 47.2%, and 23.3%. Assessment of reliability scores for five selected articles in each group showed that there were statistically significant differences between common readers and dermatologists (p<0.05). CONCLUSION: The results of this study suggest that closer monitoring of the media is required to supply easily accessible, balanced, and trustworthy information regarding alopecia.